Descentralización y desarrollo económico local: ¿puede la descentralización ayudar al desarrollo económico local y la reducción de la pobreza en el Perú? - Bustamante Belaunde, Claudia (2009)
This paper examines the link between decentralization and local economic development and poverty alleviation. It looks at the case of Peru because of its long history of centralization, and specifically at two regions that are performing differently within the country: Lambayeque and Huanuco. This paper proposes that the link is positive when the devolution of resources and responsibilities is accompanied by capacity building efforts. This is tested by a quantitative and qualitative analysis of the two regions. Although the findings are not definitive, especially due to problems measuring decentralization, they point towards the conclusion that a minimum level of human capital is needed in order to transform decentralization into economic development.